Pengembangan Permainan Tradisional Cak Lingking Pecahan Berbantuan Model Cooperative Learning Type Pair Checks - Septiana, Sindy; Feri Ardiansah; Iis Juniati Lathiifah (JBES (Journal Basic Education Skills), 2025)
This research was motivated by the lack of student motivation to complete mathematics practice questions, especially questions in story form. It aims to produce teaching materials in the form of the traditional game of cak linking fractions assisted by a valid and practical cooperative learning type pair checks model. This research is research and development (R&D) research that uses development procedures by the Borg and Gall model. Research steps include potential and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, and mass production. The subjects in this research were class VI students at SDN 18 Parittiga. The data collection techniques used were interviews and questionnaires. This research produces the traditional game media, Cak Lingking, with fractions assisted by a cooperative learning model type, pair checks with the characteristics of images of the game arena designed in the form of fractions, more than one number of uncek as a throwing tool, and story questions presented based on events in everyday life. Based on this research, the average score for the percentage of validation from media experts, materials, and teacher responses was 89.45% (very valid), and the average score for the practicality of student responses in small-scale trials and large-scale trials was 91% (very practical). So, the traditional game of cak lingking fractions assisted by the cooperative learning type pair checks model developed is declared valid and practical.